Rhetoric and Logical Argumentation of the Famous Preacher KH. Anwar Zahid - Linda Nurazizah (Kawakib: Journal of Multidisciplinary Research, 2024)
Quoting the book on the science of preaching by Prof. Dr. Moh. Ali Aziz. M. Ag,. The obligation to preach, as stated by A. Hasyimi, is not actually a special group task where other people are free from responsibility. As Muslims are given responsibilities such as prayer, zakat, fasting, so every Muslim also transfers faith in an empty heart to guide people to the straight path. The book explains that the law of preaching for Muslims can be fardhu 'ain and fardhu kifayah (together). This opinion was pioneered by Muhammad Abu Zahrah. According to him, fardhu 'ain is da'wah carried out individually. Meanwhile fardhu kifayah is da'wah carried out collectively. As we have seen, preachers who are famous throughout Indonesia, one of them is KH. Anwar Zahid, a famous preacher from East Java, originally "Wong Jowo" usually called Abah Anza, is known to be very funny and hilarious in delivering his preaching. He is a role model who is respected by his congregation. The famous jargon "Qulhu wae lek kesuwen" is acceptable to the public and the delivery of words, the language of his lectures does not make people who listen to the content of his lectures boring. With his presence in the community, he is able to make da'wah media a fun tool, especially with his videos which have been widely spread via social media and can be enjoyed by anyone who wants to study religion and who wants to put into practice the knowledge they have gained through this da'wah media.